Dynamics of the incidence of benign breast disease at the regional level - O. Yu. Sevostyanova; T. V. Chumarnaya; N. E. Sevostyanova; D. A. Demidov; A. V. Vorontsova; T. A. Oboskalova (Опухоли женской репродуктивной системы, 2023)
Background. The analysis of the incidence of benign breast disease (BBD) allows you to control the prevalence of the disease in the population and plan medical care.Aim. To study the incidence and prevalence of BBD on the example of the Sverdlovsk region in 2012–2021 and Yekaterinburg in 2012–2020.Materials and methods. An observational epidemiological retrospective study of the incidence of BBD in women aged 18 years and more was conducted. To calculate the indicators, we used the form of Federal statistical observation No. 12 for Yekaterinburg and recommendations by the Federal State Statistics Service, Russian Research Institute of Health. We analyzed the indicators of the incidence of BBD in the Sverdlovsk region, published on the websites of the Ministry of Health of Russia and the Russian Research Institute of Health. Information on the number of women examined for oncopathology was obtained from Form No. 30 “Information about a medical organization” in 2016–2020.Results. The incidence of BBD in the Sverdlovsk region increased in 2013–2019 and Yekaterinburg 2015–2019 compared to 2012 (p <0.001). During the pre-pandemic period, the average growth rate of the indicator was 5.20 % in the region, 7.60 % in the city. The incidence of BBD in the city annually exceeded the regional indicator in 2012–2019 (p <0.028). The prevalence of BBD followed the trends of the incidence (p <0.001). The average growth rate of the total incidence in the region was 7.55 %, in the city – 9.57 %. A decrease in incidence rates in the region and the city in 2020 compared to 2019 was incidence (p <0.001). A positive correlation was established between the number of cases of newly diagnosed ВВD and the number of women examined for oncopathology in the region (r = 0.924 at p = 0.025) and the city (r = 0.900 at p = 0.037).Conclusion. The incidence and prevalence of BBD in the female population of the region and the city significantly increased in the pre-pandemic period. There was a decrease in indicators due to the massive and rapid spread of a new coronavirus infection and restrictive measures aimed at containing it in 2020–2021.